Unveiling Faculty Performance through Student Eyes: A Comparative Study of Perspectives - Dipak Mahat (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main purpose of the study was to identify and compare the faculty's performance through the perception of students between Master of Business Studies (MBS) and Master of Business Management (MBM). Method: Study used a cross-sectional time horizon and objectivism methodology. The research participants consisted of 62 post-graduate students who were selected using a combination of convenient and simple random sampling methods. The collected data were analysed using SPSS software. Results: This study explores the faculty's performance from four viewpoints: knowledge of the subject, learning environment, relationships and motivation, and time. Result distinguishes the performance of MBS and MBM faculty. Measure four null hypotheses between MBS and MBM student’s perception. The study's results reveled that MBM faculty's performance is significantly more effective than MBS faculty. Novelty: Research attempt to provide unique viewpoints on students' evaluations of teacher performance, hence improving an understanding of educational dynamics within Nepal higher education system